Türkiye Büyük Millet Meclisi’nde Grubu Bulunan Partilerin Programlarında Çevre ve Sürdürülebilirlik Kavramlarının Karşılaştırmalı Analizi - (:unkn) unknown (My University, 2019)
Öncelikli hedefleri iktidarı kazanmak olan siyasi partiler, demokrasininönemli aktörlerindendir. İktidar olmak için oy beklediği kitleye karşı çeşitlivaatlerde bulunan partilerin bu vaatleri âdeta anayasa niteliğinde olan partiprogramlarında yer alır. Programlar; toplu eylem planlarını içeren, açık venet şekilde hazırlanmış, kitlelere verilmiş sözler bütününü oluşturan özgünve kolektif çalışmanın ürünü belgelerdir. 21. yüzyılın siyasi ve sosyal ortamıgöz önüne alındığında ‘çevre’ ve ‘sürdürülebilirlik’ parti programlarında yeralması gereken konuların başında gelir. Bu makalede, Türkiye Büyük MilletMeclisi’nde grubu bulunan partilerin programlarında ‘çevre’ ile‘sürdürülebilirlik’ kavramlarının durum ve bağlamları incelenecektir.Araştırmada yöntem olarak ‘Literatür Taraması’ ve ‘Söylem Analizi Tekniği’uygulanmıştır.

Political parties whose primary objective is to come into power are significant actors of democracy. Parties make various promises to their voters to come into power and these promises are involved in the programmes of the parties which are almost like the constitution. The programmes are documents which are the production of the original and collective work that include collective action plans, have been prepared clearly and openly and consist of the promises made to the voters. Considering the political and social environment of the 21st century; 'environment' and 'sustainability' come at the forefront of issues that should be included in the programmes of the parties. This article will analyze the conditions and contexts of the concepts of 'environment' and 'sustainability' in the programmes of the parties that have a group in the Turkish Grand National Assembly. In the study, 'Literature Review' and 'Discourse Analysis Technique' have been used as a method.
A Comparative Analysis of the Concepts of Environment and Sustainability in the Programmes of the Parties That Have a Parliamentary Group in the Turkish Grand National Assembly
Keywords: İletişim